Representasi Bapak dalam Film Pendek Berjudul “BAPAK” (Analisis Semiotika John Fiske) - Althaf, Muhammad Alfito (UMSU, 2025)
In patriarchal culture, fathers are often considered as the head of the family who is responsible for the economic welfare and the main decision maker in the household. As time goes by, perceptions of the figure of the father also vary greatly due to the influence of the culture in which he is located. This study aims to represent the figure of the father in Javanese culture through a short film entitled